Tourism density effect on environmental performance index: evidence in ASEAN countries - Jain Yassin; Sarma Aralas; Danie Eirieswanty Kamal Basa (2020)
The purpose of this current study is to assess the effect of tourism density on the environmental performance index on 10 ASEAN countries from 2002 to 2017. This study adopted panel data regressions with the Driscoll and Kraay standard. This method accounts for cross-sectional dependence, heteroskedasticity, autocorrelation, and the possible correlation between countries when observing the environmental performance index and tourism density. Empirical results found a statistically significant and negative relationship between the tourism density index and the environmental performance index in 10 ASEAN countries. This result implied that an increase in the tourism density index will deteriorate the environmental performance index. The results of this study underline the need for sustainable tourism policies and practices in tourism destinations to be executed by the local stakeholders and policymaker to accelerating the Sustainable Development Goals (SDGs) in ASEAN countries. In addition, this study offers justification for the policymaker to give careful attention to the carrying capacity of a tourist destination.